Zhodnocení finanční situace Delap, s. r. o. a návrhy na její zlepšení - Strnadová, Martina (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Bakalářská práce se zabývá především finanční analýzou podniku Delap, s.r.o. Hlavním úkolem je zhodnotit finanční zdraví podniku a v případě zjištění problémových oblastí navrhnout opatření pro zlepšení jejich situace. Analýza je zhotovena na základě účetních dat za období 2010-2013 pomocí vybraných metod, které byly pro toto posouzení určeny.

Bachelor thesis mainly deals with the financial analysis of the company Delap, Ltd. The main task is to evaluate the financial health of the company and in a case of detection of problem areas to propose measures to improve their situation. The analysis is made on the basis of accounting data for the period 2010-2013 using the selected methods, which were designed for this assessment.
Evaluation of Financial Situation in Delap, s. r. o. and Proposals to its Improvement
Keywords: Finanční analýza; finanční zdraví; horizontální analýza; vertikální analýza; likvidita; rentabilita; zadluženost; poměrová analýza.; Financial analysis; financial health; horizontal analysis; vertical analysis; liquidity; profitability; indebtedness; ratio analysis.